Lawyers’ duty to court - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Malaysia Sdn. Bhd., 2025)
It must be emphasised that apart from the failure to abide by professional ethics, there are other circumstances that may justify disciplinary proceedings against members of the legal profession and these include non-compliance with the provisions of the LPA and any Rules or Regulations made thereunder; being convicted of a serious offence, charging clients manifestly excessive fees, inordinate delay in handling a client’s case, and grossly disregarding the client’s interest, among others. This chapter, therefore, discusses an advocate and solicitors several duties to the court and the consequences of its violation.